2023
DOI: 10.1186/s12933-022-01733-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin-stimulated myocardial glucose metabolic rate is associated with reduced estimated myocardial energetic efficiency in subjects with different degrees of glucose tolerance

Abstract: Background Alterations in myocardial mechano-energetic efficiency (MEEi), which represents the capability of the left ventricles to convert the chemical energy obtained by oxidative metabolism into mechanical work, have been associated with cardiovascular disease. Although whole-body insulin resistance has been related to impaired myocardial MEEi, it is unknown the relationship between cardiac insulin resistance and MEEi. Aim of this study was to evaluate the relationship between insulin-stimul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Impaired insulin sensitivity and compensatory hyperinsulinemia may represent additional pathophysiological mechanisms linking increased whole blood viscosity and depressed MEEi. It has been reported that a higher degree of insulin resistance, estimated by the HOMA‐IR index, is associated with a reduction in myocardial MEEi, 41 and that an impairment in insulin‐stimulated myocardial glucose metabolism, measured by dynamic positron emission tomography with 18F‐fluorodeoxyglucose combined with euglycemic–hyperinsulinemic clamp, is associated with reduced myocardial MEEi in individuals with different degrees of glucose tolerance 55 . There is also substantial evidence showing that impaired insulin sensitivity is associated with higher values of haematocrit, the main determinant of blood viscosity, increased blood viscosity and higher erythrocyte aggregability 56–59 .…”
Section: Discussionmentioning
confidence: 99%
“…Impaired insulin sensitivity and compensatory hyperinsulinemia may represent additional pathophysiological mechanisms linking increased whole blood viscosity and depressed MEEi. It has been reported that a higher degree of insulin resistance, estimated by the HOMA‐IR index, is associated with a reduction in myocardial MEEi, 41 and that an impairment in insulin‐stimulated myocardial glucose metabolism, measured by dynamic positron emission tomography with 18F‐fluorodeoxyglucose combined with euglycemic–hyperinsulinemic clamp, is associated with reduced myocardial MEEi in individuals with different degrees of glucose tolerance 55 . There is also substantial evidence showing that impaired insulin sensitivity is associated with higher values of haematocrit, the main determinant of blood viscosity, increased blood viscosity and higher erythrocyte aggregability 56–59 .…”
Section: Discussionmentioning
confidence: 99%
“…The results might be reflected by higher triglyceride level as well as elevated level of liver enzymes and lower liver CT value (Additional file 1: Table S1). Cardiac insulin resistance is considered to have a predominant role in determining alterations of left ventricular mechano-energetic performance [42]. However, no significant correlation was found between HOMA-IR and myocardial CT value or cardiac function in the In addition, another study reported that obesity-or metabolic syndrome-related alterations in lipid metabolism increase myocardial fat content, epicardial fat thickness, inflammation and oxidative stress which ultimately leads to cardiac lipotoxicity and diastolic dysfunction [43].…”
Section: Relationships Between Myocardial Fat and Obesity Related Fac...mentioning
confidence: 99%
“…Fasting plasma glucose (FPG) is closely related to diabetes, not only as an indicator of pancreatic function and insulin resistance [ 7 ] but also as a diagnostic criterion. The normal range for FPG was set at 3.9–6.1 mmol/L by the American Diabetes Association (ADA) in 1997 [ 8 ] and by the World Health Organization (WHO) in 1999 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%